DAMPAK MATERIALISM VALUE DAN INFORMASI PRODUK TERHADAP MINAT BELI PRODUK DONASI - Tambunan, Maria Anastasia; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2017)
This research was conducted to test the effect of Materialism Value and information of product variable to Buying Interest of Charity Product. This research also aimed to analyze the difference of high materialism value and low materialism value to the buying interest of charity product, whether materialism value level can influence buying interest of charity product and also analyzing whether the information of charity product that have been given to the participants can influence the relationship between materialism value with buying interest charity product. The research methodology used on this research is quasi field experiment. The number of participants used was 80 participants, consisting of 40 participants for the group that obtained the information of the charity product and 40 participants for the group who did not got the information of charity product. The data analysis test used is Two Ways Anova with factorial design of two independent variables and independent t test to know the comparison between the experimental research group. The result of the analysis showed that materialism value did not affect the buying interest of charity product, information of charity product has an influence on buying interest of charity product, and the interaction between materialism value and information of charity product did not affect to buying interest of charity product. The statistical results showed that H1 and H2 are accepted while H3 and H4 were rejected. The statistical results showed the differences in buying interest in charity product among high materialism value groups and low materialism value groups that obtain information of charity product.